Kebermaknaan Hidup Perempuan Single Parent di Tengah Masayarakat (Studi Fenomenologis pada Perempuan Single Parent di Daerah Jenggawah Kabupaten Jember) - Indah; Siti Nurmaidah (Jurnal Al-Tatwir, 2022)
Having a peaceful married life is everyone's dream. Being able to build a harmonious household is happiness for every woman. But the circumstances that occur are often beyond human expectations. Experiencing failure in marriage for women sometimes makes their life meaningless. When someone experiences meaningless, of course he will try to find a way to give meaning to his life. After the failure of marriage, women become single parents or single parents. Being a woman with a single parent status is not an easy thing to do, in addition to changing their status to being a single parent, they also have to carry out dual roles as a mother and a father for their children. Getting negative stigma from the wider community is also often a burden in life. Positive support will help them find meaning in their lives. This study was conducted to see the meaning of life in women who have the status of a single parent. The number of subjects in this study were 3 women as single parents located in the Jember area, with different separation backgrounds. The results showed that the three subjects experienced suffering after divorce and the death of their husbands, including full responsibility for their children. But with lots of support, I feel calmer and find the meaning of life even though I have to live life as a single parent.